The future of financial regulation - MacNeil, Iain; O'Brien, Justin (Peter Justin) (Hart, 2010)
The Future of Financial Regulation is an edited collection of papers presented at a major conference at the University of Glasgow in spring 2009, co-sponsored by the Economic and Social Research Council World Economy and Finance Programme and the the Australian Research Council Governance Research Network. It draws together a variety of different perspectives on the international financial crisis which began in August 2007 and later turned into a more widespread economic crisis following the collapse of Lehman Brothers in the autumn of 2008. Spring 2009 was in many respects the nadir since val.